(untitled) (Academicia Globe: Inderscience Research, 2021)
The article provides a statistical analysis of small business and private entrepreneurship, economic development and legal framework, taxation on income and single tax payment. Creation of new jobs to ensure a stable and flexible development of small business in the Republic of Uzbekistan in the conditions of market conditions.